EXPLANATION
As the sum is given by the arithmetic sequence:
![S_n=(3n(n-33))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/3qs7zpdpxoc60qrme5g3dgz0b8t2569d3u.png)
a)
Applying the sumatory to the first 10 terms:
![S_(10)=(3\cdot10(10-33))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/hc9vs34brj6lni9gbnbhpiubpbj63gln71.png)
Subtracting numbers:
![S_(10)=(3\cdot10\cdot(-23))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/yytu0ltj5gzbc0x7duzh0lqenj52l5k5no.png)
Multiplying numbers:
![S_(10)=(-690)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/nk3u5iyu31d55e4qjemrfa63zhxz8pe87q.png)
Simplifying:
![-345](https://img.qammunity.org/2023/formulas/mathematics/college/jokhq8bxwdn8rurehrmjwhdlgqez59rl8y.png)
b) The first term is given as shown as follows:
![S_1=(3\cdot1\cdot(1-33))/(2)=(-96)/(2)=-48](https://img.qammunity.org/2023/formulas/mathematics/college/g5n67ti81kcekhtwif1k1kxneaezcfyvdr.png)
We can get the common difference by computing each subsequent number of the sequence and subtracting to the last one as shown as follows:
![a_2=S_2-(-48)=(3\cdot2\cdot(2-33))/(2)-(-48)=-93+48=-45](https://img.qammunity.org/2023/formulas/mathematics/college/558tphkpi4gl1okup5rz4q94g8ga0r7cvq.png)
Now, subtracting -45 to the first term -48 give us:
-45 - (-48) = -45 + 48 = -3
In conclusion, the common difference is -3